2019
DOI: 10.5334/joh.14
|View full text |Cite
|
Sign up to set email alerts
|

On the Economic Value of Open Source Hardware – Case Study of an Open Source Magnetic Resonance Imaging Scanner

Abstract: Increasing maturation and dissemination of easy-to-use and affordable means of digital production (e.g. 3D printing), access to these in makerspaces and FabLabs as well as powerful tools and online platforms for virtual and collaborative product design enabled the highly efficient and innovative mode of open source to spill over from software to hardware. Open source technology has enormous potential to spur innovation and enhance technological literacy and thus contribute to socioeconomic and ecological susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
(31 reference statements)
0
19
0
Order By: Relevance
“…This horizontal scaling will be accomplished by national and state-level funding being spent only once for development of scientific equipment and then an immediate ROI is realized by the digital replication of the devices throughout the country for the costs of materials. For example, Moritz et al quantified cost savings and as a result the value of an open source magnetic resonance imaging device (MRI) currently under development by the Open Source Imaging Initiative and found that depending on the scenario and the valuation method, savings for healthcare systems from US$1.8 million up to US$222 million per year are possible in the near future making the case for public funding and private investment in open source technology development [87] . There is a clear high ROI for medical open source technologies as well as for the sciences [88] .…”
Section: Discussionmentioning
confidence: 99%
“…This horizontal scaling will be accomplished by national and state-level funding being spent only once for development of scientific equipment and then an immediate ROI is realized by the digital replication of the devices throughout the country for the costs of materials. For example, Moritz et al quantified cost savings and as a result the value of an open source magnetic resonance imaging device (MRI) currently under development by the Open Source Imaging Initiative and found that depending on the scenario and the valuation method, savings for healthcare systems from US$1.8 million up to US$222 million per year are possible in the near future making the case for public funding and private investment in open source technology development [87] . There is a clear high ROI for medical open source technologies as well as for the sciences [88] .…”
Section: Discussionmentioning
confidence: 99%
“…(6) Developed by software coding communities (7) and maker cultures,(8) these approaches are generally conducted in an open collaborative manner where individuals share their design tools and processes (9) so that anybody may build their own products. (10) Proponents list many advantages, including reduced costs,(9, 10) fast innovation cycles, (11) adaptable designs(10) as well as improved accessibility, sustainability,(9) interoperability, safety, and security. (10) Of note are the #WeAreNotWaiting community, where patients and caregivers develop open DIY health technologies for diabetes management, (6) and the field of open DIY assistive technologies, (12) which is driven by more accessible 3D printing and by many users' lack of access to (13) or satisfaction with their devices.…”
Section: Introductionmentioning
confidence: 99%
“…(10) Of note are the #WeAreNotWaiting community, where patients and caregivers develop open DIY health technologies for diabetes management, (6) and the field of open DIY assistive technologies, (12) which is driven by more accessible 3D printing and by many users' lack of access to (13) or satisfaction with their devices. (14) Though open DIY initiatives remain marginal in the health field, (11) they are drawing increasing academic attention for their capacity to innovate and their potential to improve healthcare. (6,13,(15)(16)(17)(18)(19) For some scholars, this bottom up movement (16) indicates how the provision of healthcare is now shared between institutions, providers, and citizens who are actively involved in finding solutions to their problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RepRap technology in turn catalyzed millions of free and open-source 3D-printable designs and created a consumer (or prosumer) form of distributed manufacturing [12][13][14]. RepRaps and their derivatives are now used to manufacture a wide range of products from household items [15][16][17][18] to high-end scientific tools [19][20][21][22][23], generally far less expensively than available commercially [24][25][26]. The business community understands the widespread impact this potential shift in manufacturing represents [27][28][29][30][31][32][33] [65], composites [66] and various mixtures with waste wood fiber [47,63,67,68].…”
Section: Introductionmentioning
confidence: 99%